Військова еліта Української Держави: еволюція політичних лояльностей - Пиріг, Р. (Український історичний журнал, 2018)
Досліджуються зміни політичних лояльностей військових діячів, які стали
на службу гетьманату П.Скоропадського. Висвітлюється вплив революційних подій на процеси національної самоідентифікації частини офіцерства, яке взяло участь в українізації армії, ставши першими командними кадрами
військових формувань УНР. Розкрито фактор ситуативності політичної позиції військовиків щодо національних державних утворень, роль соціальних імперативів у виборі місця служби, нівелювання військової присяги під впливом
зміни політичних обставин. Показано домінування у свідомості колишнього
імперського ґенералітету ідеї відродження «великої Росії», котра обумовила
після падіння гетьманської держави їх перехід до лав Добровольчої армії. Персоніфіковано зміни політичної лояльності ґенералів та адміралів Української Держави на рівні керівництва військового й морського міністерств, корпусів і
дивізій. Визначено стримуючу роль німецького військового командування щодо
розбудови української армії. З’ясовано погляди гетьмана П.Скоропадського на
кадрові засади створення збройних сил України, зокрема їх військово-морського сеґменту. This article is a research on the transformation of the political loyalties of the
military leaders who served in the Hetmanate of P.Skoropadskyi. It focuses on
the impact of the revolution on the formation of the national identity when a part
of the high rank military officers took part in the Ukrainization of the army and
became the first commanding personnel of the military forces of the Ukrainian
People’s Republic (UPR). The article reveals the factor of contextuality in the political
position of the military personnel in regards to national state formations, the role of
the social imperatives in choosing a place of service, the levelling of the military oath
by the change of the political circumstances. The article shows that the idea of the
renaissance of the "Great Russia" was dominant in the minds of the former imperial
generalship that accounted for their joining the Volunteer Army forces after the
demise of the Hetmanate. The article personifies the changes of the political loyalty of
the generals and navy admirals of the Ukrainian State on the level of the leadership
of the military and marine ministries, corps and divisions. The article identifies the
suppressing role of the German military leadership in the process of building of
the Ukrainian army. It defines Hetman P.Skoropadskyi’s views on the staffing policy
when creating the military forces of Ukraine, its naval forces in particular.